Dėl veiksmažodžių su formantais -sk-, -šk- - Jakulis, Erdvilas (Baltistica, 2005)
ON THE LITHUANIAN VERBS WITH ROOT-FINAL FORMATIVES -sk-, -šk-The article presents the analysis of the etymology of the verbs Lith. viskė́ti, tuskė́ti and tvaskė́ti. The attempt of N. Ostrowski to derive these verbs from the verbs with the suffix -sėti using the method of metathesis is proven false for the following reasons:1) the so called „metathesis“ ST+V → TS does not have any basis in terms of articulation;2) if such „metathesis“ had happened, other problems of verb derivation and chronology would have emerged:a) metathesis does not explain other verbs having ST-finals;b) verbs with suffix -sėti, that underwent transformation after metathesis, should have disappeared, nevertheless they survived (e.g. viksė́ti, tuksė́ti, tvaksė́ti);c) verbs with the suffix -sėti are derived from onomatopoeic interjections (sometimes verbs) and are relatively new, whereas tekėti, teka type verbs are not derivatives, some of them are inherited from Indo-European.
Keywords: lietuvių kalba; veiksmažodis